A mobile teletrauma system using 3G networks. - Chu, Y. (IEEE Transactions on information technology in biomedicine)
This paper introduces a cost-effective portable teletrauma system that assists health-care centers in providing prehospital trauma care. Simultaneous transmission of a patient's video, medical images, and electrocardiogram signals, which is required throughout the prehospital procedure, is demonstrated over commercially available 3G wireless cellular data service. Moreover, the physician can remotely control the information sent from the patient side. Such a technology will allow a trauma specialist to be virtually present at the remote location and participate in prehospital care, which improves the quality of trauma care and can potentially reduce mortality and morbidity. To alleviate the limited and fluctuant bandwidth barriers of the wireless cellular link, the system adapts to network conditions through media transformations, data prioritization, and application-level congestion control methods. Experimental evaluation of the system prototype over real network conditions, transmitting different media types between the trauma patient and hospital unit, is encouraging. The teletrauma system reported in this paper is the first of its kind and it provides a basis for future enhancements.